2023
DOI: 10.3390/medicina59081438
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Associated Fatty Liver Disease (MAFLD) and COVID-19 Infection: An Independent Predictor of Poor Disease Outcome?

Abstract: Background and Objectives: Early reports on COVID-19 infection suggested that the SARS-CoV-2 virus solely attacks respiratory tract cells. As the pandemic spread, it became clear that the infection is multiorganic. Metabolic associated fatty liver disease (MAFLD) is a chronic liver disease strongly associated with insulin resistance and diabetes. The aim of this study was to assess a possible interplay between MAFLD and COVID-19 infection and its implication in COVID-19 outcome. Materials and Methods: A retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…The definite majority of already obtained data concerning the outcome of patients with COVID-19 and underlying liver disorders focus on liver steatosis. Previous observations indicated that BMI and the presence of MAFLD might constitute risk factors for a more severe course of COVID-19 [213]. The number of reports on patients with ALD infected with SARS-CoV-2 seems to be somewhat limited.…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 99%
“…The definite majority of already obtained data concerning the outcome of patients with COVID-19 and underlying liver disorders focus on liver steatosis. Previous observations indicated that BMI and the presence of MAFLD might constitute risk factors for a more severe course of COVID-19 [213]. The number of reports on patients with ALD infected with SARS-CoV-2 seems to be somewhat limited.…”
Section: Coronavirus In Ald Patientsmentioning
confidence: 99%